Factors Influencing Pregnant Women to Conduct HBsAg Tests in the Working Area of the Rohan Dalam Barito Kuala Health Center - Dian Purnama Sari (Sean Institute, 2023)
Cases of hepatitis B in Indonesia have a relatively high level, early detection of hepatitis B in pregnant women was carried out in Indonesia in 2013, starting from DKI Jakarta and continuing to grow to other provinces in the following years. In 2016, hepatitis B examination was carried out with the Rapid Diagnostic Test (RDT) Hepatitis B surface antigen (HbsAg) (SIHEPI, 2019). This study aims to determine the factors that influence pregnant women in carrying out HbsAg examinations in the Working Area of ​​the Spirit of Dalam Barito Kuala Community Health Center. This research uses a descriptive method. The population in this study were all pregnant women who had their HBsAg checked in April-July 2022 in the Working Area of ​​the Spirit of Dalam Barito Kuala Community Health Center, totaling 102 people. Some of the samples in this study were pregnant women who visited the Spirit of Internal Health Center, namely 50 respondents who came to the Lucky Raya Health Center in this study. Based on the results of the study, it was found that the highest level of knowledge of mothers in carrying out HbsAg examinations was in the low category, the education level of mothers in carrying out HbsAg examinations was the highest in the low category, the occupational category owned by mothers was the most, namely the working category, and the most role category of health workers, namely mothers who carry out an HbsAg examination because it was recommended by the health worker.